Three-level common emitter-current source inverter equipped with MPPT system for photovoltaic power converter - Suroso, Suroso; Noguchi, Toshihiko (Institute of Advanced Engineering and Science, 2025)
Common emitter-current source inverter (CE-CSI) has unique features with its common emitter structure of its power switches. Hence, instead of its simpler power supply for gate drive circuits, it also allows higher switching operation because of zero gradient voltage of its power switches. One of interesting applications of current source power inverter is for photovoltaic (PV) power converter. This paper discussed the three-level CE-CSI equipped with current based incremental resistance maximum power point tracking (MPPT) system as a new alternative for PV system power converter. Test results revealed some characteristics of PV power conversion using this inverter. Moreover, in order to investigate the system performance approaching real condition, testing during partial shading condition of PV modules were also conducted. Test results verified the efficacy of the incremental resistance based MPPT algorithm implemented in the CE-CSI circuits for increasing the performance of PV power generation.